Nicotinic Receptors - Lester, Robin A.J (The Receptors, 2014)
A comprehensive overview of nicotinic receptors that addresses their history from crystal structure to behavior as well as their implications in disease and potential as therapeutic targets. It includes background information on all subtypes of nicotinic receptors, the most recent information on the distribution throughout the nervous system, and discussion of their implications in learning and memory, addiction, and neurological and psychiatric disease such as Alzheimer's and Parkinson's. Takes advantage of several recent developments in the fields of optogenetics, viral expression, and gene analysis to focus on current knowledge on the functional aspects of nicotinic receptors.